2008
DOI: 10.1093/ietisy/e91-d.12.2888
|View full text |Cite
|
Sign up to set email alerts
|

Objective Pathological Voice Quality Assessment Based on HOS Features

Abstract: SUMMARY This work proposes new features to improve the pathological voice quality classification performance. They are the means, the variances, and the perturbations of the higher-order statistics (HOS) such as the skewness and the kurtosis. The HOS-based features show meaningful differences among normal, grade 1, grade 2, and grade 3 voices classified in the GRBAS scale. The jitter, the shimmer, the harmonic-to-noise ratio (HNR), and the variance of the short-time energy are utilized as the conventional feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…In this paper, new parameters to describe the characteristics of breathy and rough voices are introduced. In previous studies, HOSs have shown promising results in the characterization of pathological voices [24,25]. Also, in a large number of published papers, the LPC residual has been shown to be able to classify between normal and pathological voices [14,28].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this paper, new parameters to describe the characteristics of breathy and rough voices are introduced. In previous studies, HOSs have shown promising results in the characterization of pathological voices [24,25]. Also, in a large number of published papers, the LPC residual has been shown to be able to classify between normal and pathological voices [14,28].…”
Section: Resultsmentioning
confidence: 99%
“…While previous work in the area of speech analysis, voicing classification, and pitch estimation have attempted to exploit parameters based on the HOSs of speech signals, little has been done in providing an analytical framework for disordered voice analysis [20][21][22][23][24][25]. Alonso et al proposed the following HOS-based parameters: the interference value of the bicoherence index, the relative values of the high and low frequency energy of the onedimensional bicoherence index, the value of their interference, the variation of the estimated noise by means of the module of the bispectrum, the variation of the noise obtained through the same technique taking into account in this case the phase information, and the interference of the kurtosis [23].…”
Section: Hos Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…If it is a little larger deviation from an average value, it may have an effect on the performance degradation of voice analysis and recognition [14]- [15]. In case of most welfare smart devices, the elderly signals have been neglected due to interface which does not take into account the elderly [6].…”
Section: Discussionmentioning
confidence: 99%